Bank Perekonomian Rakyat Syariah (BPRS): Analisis Bibliometrik dan Kajian Literatur Sistematis - Muhammad Isman Almaududi; Pranoto Effendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to map and analyze the development of research on Islamic Rural Banks (BPRS) using a bibliometric approach and a systematic literature review (SLR). BPRS are Islamic financial institutions that play a crucial role in supporting financial inclusion, particularly in the micro and small sectors; however, academic studies on their role and performance remain limited and have yet to be comprehensively documented. This research employs bibliometric methods using software such as VOSviewer to analyze articles published in scientific journals indexed in Google Scholar. The analysis covers publication trends, citation patterns, author collaborations, and the identification of key topics examined within the context of BPRS. Furthermore, an SLR was conducted to delve into key themes such as risk management, efficiency, contributions to the regional economy, and compliance with Sharia principles. The findings indicate that although interest in the BPRS topic has increased in recent years, more in-depth research on service innovation, digitalization, human resources, and corporate governance is still highly necessary. This study provides recommendations for future research directions to strengthen the literature on BPRS and enhance the understanding of its contribution to the development of the Sharia-based economy.